2015
DOI: 10.1080/09205063.2015.1068606
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic mineralization of collagen fibrils induced by amine-terminated PAMAM dendrimers – PAMAM dendrimers for remineralization

Abstract: In this study, we successfully induced biomimetic mineralization within type-I collagen fibrils using G3-PAMAM-NH2. This strategy may serve as a potential therapeutic technique for restoring completely demineralized collagenous mineralized tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…Previous studies showed that some calcium phosphate compounds were only suitable for remineralizing the partially-demineralized dentin, which relied on the epitaxial deposition of calcium and phosphate ions over remnant crystallites [12,17]. In some clinical situations, dentin is completely demineralized and the collagen fibril is exposed.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies showed that some calcium phosphate compounds were only suitable for remineralizing the partially-demineralized dentin, which relied on the epitaxial deposition of calcium and phosphate ions over remnant crystallites [12,17]. In some clinical situations, dentin is completely demineralized and the collagen fibril is exposed.…”
Section: Discussionmentioning
confidence: 99%
“…However, PAMAM was found to have the ability to remineralize not only the partially-demineralized dentin, but also collagen fibrils. This is because PAMAM is a biomimetic analog to NCPs and can induce biomimetic remineralization based on a particle-based crystallization concept [12,22]. PAMAM can perform its function when bonded to a surface and dentin collagen fibers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations